(3aJM GdHGQi HTQM UMjM GdHNGQis - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s; (3CHh YHO Gddg eMeO Hf GdMSf Hf aQbO, GdTjHGfj,J (B189 (3g` s
(3ChdgG (B:s
(3jHOC CKfGA cJGH GdCOH bHd HGH eG fgi Yf GdSHGH hGddYf Hbhdg (B:" (3bO JbOe TQM GdMOjK eSJhai ai cJGH GdML hYfO eSde ef MOjK CHj gQjQI(B: (3cd GdeSde Ydi GdeSde MQGe Oeg hYQVg heGdg s
(3BNQgG (B:s
(3jfJgi CKfGA HGH ef JQc bJGd GdNhGQL ddJCdja hdFdG jfaQ GdfGS Yfg , ef cJGH ESJJGHI GdeQJOjf hGdeYGfOjf hbJGdge , Hbhdg (B" (3hGddg Efi dCQLhG Cf jchfhG gDdGA Gdbhe aEfge bO SachG GdOe GdMQGe hEfeG QChG Cfg ai TQM GdfGS bGd adeG (B" s
(3HgG fXGe GdJYbjHIs
(3LRA efgs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B80s
Keywords: (3GdMOjK h GdeUWdMs